2020
DOI: 10.1111/cogs.12833
|View full text |Cite
|
Sign up to set email alerts
|

Who Is to Blame? Children's and Adults' Moral Judgments Regarding Victim and Transgressor Negligence

Abstract: Research has documented that individuals consider outcomes, intentions, and transgressor negligence when making morally relevant judgments (Nobes, Panagiotaki, & Engelhardt, 2017). However, less is known about whether individuals attend to both victim and transgressor negligence in their evaluations. The current study measured 3-to 6-year-olds (N = 70), 7-to 12-year-olds (N = 54), and adults' (N = 97, ages 18-25 years) moral judgments about scenarios in which an accidental transgression occurred involving prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 38 publications
2
21
1
Order By: Relevance
“…and to transgressions that vary in the severity of the harm that is caused. It may also be interesting to explore intergroup forgiveness in response to transgressions that were accidental and intentional (Killen et al, 2011; Young & Saxe, 2009) and to transgressions where the transgressor was trying to be careful or was being negligent (Mulvey et al, 2020; Nobes et al, 2016; Nobes et al, 2017). Finally, it may be interesting to examine forgiveness in situations where the transgression is repeated, such as in instances of bullying.…”
Section: Discussionmentioning
confidence: 99%
“…and to transgressions that vary in the severity of the harm that is caused. It may also be interesting to explore intergroup forgiveness in response to transgressions that were accidental and intentional (Killen et al, 2011; Young & Saxe, 2009) and to transgressions where the transgressor was trying to be careful or was being negligent (Mulvey et al, 2020; Nobes et al, 2016; Nobes et al, 2017). Finally, it may be interesting to examine forgiveness in situations where the transgression is repeated, such as in instances of bullying.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that preschoolers used a form of outcome‐based reasoning to form impressions of recipients, a focus not altogether captured in previous discussions of intention‐outcome reasoning (see Mulvey et al., 2020). Children may have matched the outcome of each scene to the actor rather than to the recipient and used this strategy to conclude that the recipient does not deserve blame.…”
Section: Discussionmentioning
confidence: 99%
“…These negative perceptions of recipients of negative acts manifest when adults perceive that recipients of negative acts are to blame for their own misfortune because they are irresponsible (e.g., Adams‐Price et al., 2004) or have otherwise ‘invited’ the harm done against them (Cortina et al., 2018). In the absence of either real or perceived negligence (e.g., Mulvey et al., 2020), it is unclear how young children's inferences about the recipients of negative behavior compare to inferences about the recipients of positive behavior. Children may attend selectively to frequency information to evaluate recipients when valence is salient (e.g., Boseovski & Lee, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a recent study showed that both children and adults attend to transgressor's negligence but also to victim's negligence (Mulvey et al, 2020).…”
Section: Judging Accidental Harmmentioning
confidence: 99%